2011
DOI: 10.1158/1078-0432.ccr-11-0071
|View full text |Cite|
|
Sign up to set email alerts
|

Reduced miR-128 in Breast Tumor–Initiating Cells Induces Chemotherapeutic Resistance via Bmi-1 and ABCC5

Abstract: Purpose: Tumor-initiating cells are resistant to chemotherapy, but how microRNAs play a role in regulating drug resistance of breast tumor-initiating cells (BT-IC) needs to be clarified.Experimental Design: Lentivirus-mediated miR-128 transduction was done in BT-ICs, enriched by mammosphere cultures or CD44 þ CD24 À fluorescence-activated cell sorting. Apoptosis and DNA damage were determined upon treatment with doxorubicin. Expression of miR-128 in breast cancer tissues was examined by in situ hybridization a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
140
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(146 citation statements)
references
References 37 publications
(41 reference statements)
4
140
0
2
Order By: Relevance
“…Previous studies have shown that miR-128(-3p) acts as an oncogene in malignancies such as acute leukemia, 24,25 breast cancer 13,[26][27][28] and lung cancer. 14 However, this miRNA has also been described to have tumor suppressive functions in other cancer entities (for an overview, refer to Online Supplementary Table S4).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that miR-128(-3p) acts as an oncogene in malignancies such as acute leukemia, 24,25 breast cancer 13,[26][27][28] and lung cancer. 14 However, this miRNA has also been described to have tumor suppressive functions in other cancer entities (for an overview, refer to Online Supplementary Table S4).…”
Section: Discussionmentioning
confidence: 99%
“…Some miRNAs are indicators of drug resistance and confer resistance to a variety of chemotherapeutic drugs [9,10,11]. MiR-218 is expressed in several carcinomas and plays critical roles in carcinogenesis, cancer proliferation and cancer metastasis.…”
mentioning
confidence: 99%
“…The regulatory mechanism of miR‐128‐3p seems to be relevant also in breast cancer patients as our analysis suggests that miR‐128‐3p is lower expressed in nonluminal breast cancer compared to luminal‐like subtypes. Low‐level expression of miR‐128‐3p also correlates with poor clinical outcome of patients with breast cancer (Qian et al ., 2012; Zhu et al ., 2011). Other studies have shown that miR‐128‐3p is also lower expressed in other tumor tissues and that its overexpression inhibits tumor cell proliferation, angiogenesis, and invasion (Evangelisti et al ., 2009; Hu et al ., 2014; Palumbo et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs regulate signaling pathways at the post‐transcriptional level and are frequently deregulated in breast cancer. It has been shown that aberrantly expressed miRNAs promote cancer development, metastasis formation, and potently induce drug resistance in both tumor cells and cells of the tumor microenvironment (Bott et al ., 2017; Breunig et al ., 2017; Dvinge et al ., 2013; Tang et al ., 2012; Zhu et al ., 2011). In a previous study, we have identified a tumor‐suppressive function of the miR‐520/miR373 family by targeting TGFBR2 in breast cancer cells (Keklikoglou et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%